2001
DOI: 10.1017/s0144686x01008145
|View full text |Cite
|
Sign up to set email alerts
|

Volunteerism among older people with arthritis

Abstract: Research attention has turned towards investigating the motivations and experiences of those who volunteer under conditions that benefit both giver and recipient. The purpose of this paper is to examine the motivation of 22 older volunteers as they embarked on training to become lay leaders of an arthritis self-management programme. Data were collected through semi-structured telephone interviews at two points in time, before training and six weeks after training. Volunteerism was motivated by three key needs:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 53 publications
(55 citation statements)
references
References 0 publications
2
52
0
1
Order By: Relevance
“…Helping others has been associated with "improved morale, self-esteem, positive affect, and well-being" (12). The "Challenging Arthritis" (CA) course represents a special case of structured volunteering whereby both helper and recipient are likely to reap benefits from learning about managing their condition (13). The format of volunteering is prescribed; volunteers are trained to deliver a structured course using a detailed manual.…”
Section: Introductionmentioning
confidence: 99%
“…Helping others has been associated with "improved morale, self-esteem, positive affect, and well-being" (12). The "Challenging Arthritis" (CA) course represents a special case of structured volunteering whereby both helper and recipient are likely to reap benefits from learning about managing their condition (13). The format of volunteering is prescribed; volunteers are trained to deliver a structured course using a detailed manual.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is understandable that volunteers may not easily experience a sense of personal accomplishment in the course of their voluntary service. In this study, a majority of the depicted benefits from voluntary work were related to contribution to the society and opportunities to acquire knowledge and skills, which are two important aspects of benefit/reward that elderly volunteers would like to obtain from their service (Barlow and Hainsworth, 2001). Indeed, results from hierarchical regression analyses showed that among all hypothesized factors, organizational factors of perceived benefit and satisfaction from voluntary work emerged as the best predictors of the LPA dimension of burnout.…”
Section: Discussionmentioning
confidence: 98%
“…It should be noted that personal achievement in paid employment would be measured against concrete outcomes such as pay increases and promotion. Participation in voluntary work often relies on intrinsic motives such as altruism, personal development, and social responsibility (Black and DiNitto, 1990;Omoto and Synder, 1995;Barlow and Hainsworth, 2001). However, the attainment of these intrinsic goals are often difficult to evaluate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably because learning per se is important throughout adulthood. Age groups might just differ in the knowledge and skills that they consider age-relevant (Barlow and Hainsworth 2001). While learning new knowledge and skills are future-oriented for younger adults, learning social skills through volunteering may fulfill the emotionally meaningful goals for older adults.…”
Section: Discussionmentioning
confidence: 99%